Biodegradable silica rubber core-shell nanoparticles and their stereocomplex for efficient PLA toughening. (3rd May 2018) - Li, Zibiao; Muiruri, Joseph K.; Thitsartarn, Warintorn; Zhang, Xing; Tan, Beng Hoon; He, Chaobin
Abstract: In the effort to overcome the shortcomings such as brittleness and poor mechanical stability, and increase the competitive edge of renewable poly(lactic acid) PLA over conventional petroleum-based thermoplastics, silica rubber core-shell nanoparticles for effective PLA toughening were successfully synthesized by sequential ring opening polymerization (ROP). The core-shell structure was designed with silica as inner core, P(CL- m LA) as 'rubber' middle layer and terminal PDLA chains (SiO2 - r -PDLA), to facilitate the stereocomplex formation with PLLA matrix for enhanced interface control. The PLLA/SiO2 - r -PDLA nanocomposites were fabricated through solution blending-injection molding process. Nuclear magnetic resonance ( 1 H NMR and 13 C NMR) results confirmed the presence of grafted 'rubber' and PDLA chains from the surface of silica particle. In addition, PLLA/SiO2 - r -PDLA nanocomposites showed tremendous improvement in thermal and mechanical properties using differential scanning calorimetry (DSC) and tensile testing, respectively. Besides the formation of stereocomplex in the nanocomposites, a detailed study on the melt stability of these stereocomplex nanocomposites revealed a 'memorized' stereocomplex behavior, i.e., having the ability to perfectly reassemble after re-crystallization from melt (melt memory effect), when rubber segment is present. Finally, structure-deformation mechanisms were studied using scanning electron microscopy (SEM) and small angle x-ray scattering (SAXS). From SAXS, crazing was clearly observed whereas SEM revealed fibrillated structures. Thus, crazing and fibrillation are the key deformation mechanisms in PLLA/SiO2 - r -PDLA system. The exciting new fillers could open up new horizons for PLA advanced composites applications. Graphical abstract: Image 1